(untitled) (World Bulletin of Management and Law, 2024)
The article analyzes environmental problems that need to be solved in the process of realizing the goal of sustainable development of cities. The contents of the documents adopted by the international community were studied. At the same time, the norms of the state environmental policy of the Republic of Uzbekistan and the norms of national legislation on the development of open and sustainable cities were studied, and suggestions were made for their improvement.